Persepsi Pelaku Usaha Mikro Kecil Menengah (Umkm) Terhadap Inovasi Kuliner - Ismon Zakya HS; Heryudarini Harahap (Badań Perencanaan Pembangunan Dearth, Penelitian dań Pengembangan Provinsi Riau, 2016)
The objective of innovation is to improve the function, benefit, and application of sciences that has been available or produce new technologies. The study aims was to asses the perception of product, label and packaging innovation of micro, small and medium enterprises (MSMEs) as well as the association with the perceptions. The study was conducted in Meranti Islands and Kampar District. Methods of the study was cross-sectional. The number of subject was 44 MSMEs. Study showed that MSMEs with agree perception for product innovation was 93.0%, packaging innovation was 90.5%, and labeling innovation was 93.2%. Factors associated with product, labeling and packaging innovation of MSMEs perception were education and business duration. MSMEs with business > 10 years had risk for not agree 2.5 times for product, 2.4 times for labeling, and 2.5 times for packaging than MSMEs with business duration ≤ 10 years. SMEs with junior high school education or below had risk for not agree 1.7 times for product, 1.7 times for labeling and 1.8 times for packaging innovation than SMEs with senior high school or above. It was suggested that the Government of Meranti Islands And Kampar District to fasilitate product, labeling and packaging innovation for MSMEs.